Dịch chuyển hướng lên và sự khác biệt giữa các nhóm dân cư ở Việt Nam - Phạm Thị Bích, Ngọc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Over the past two decades, Vietnam has achieved remarkable economic growth, yet whether this growth has truly expanded opportunities for all groups remains an open question. This study addresses this question measuring the upward mobility index of population groups during 2002–2020, using data from the Vietnam Household Living Standards Survey (VHLSS) and the method proposed by Ray and Genicot (2023). The results show that while Kinh households exhibit a higher level of upward mobility, ethnic minority households contribute a larger proportion to the overall national upward mobility index. Rural areas also display higher mobility than urban ones, reflecting the effectiveness of rural development policies. Moreover, inter-group inequality has gradually declined, indicating a narrowing of the opportunity gap – an encouraging sign of inclusive growth. These findings underscore the importance of policies that enhance access to education, infrastructure, and employment, particularly for ethnic minorities and rural communities, to sustain upward mobility and strengthen inclusive and sustainable development.